FENOMENA PEMBERDAYAAN MANAJEMEN ORGANISASI BIROKRASI DI DAERAH - H. Abdul Rasul (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
The development of bureaucratic organization in the region today becomes an interesting phenomenon to be studied.In addition to the change of government system from the centralized menjadisistern government which emphasized on regional autonomy, can also be seen on the aspects of organizational management, especially in the context of empowerment managementorganisasi.Berbagai important role of all components of organizational management bureaucracy in the region. The results of the study also attempted to look at the problems of bureaucracy management in a region called bureaucratic